69.2k views
0 votes
Please help! need to know how to solve this Urgent!

Please help! need to know how to solve this Urgent!-example-1
User TonyY
by
5.1k points

2 Answers

4 votes

Explanation:

I dont know if this helps but that what I came up with

Please help! need to know how to solve this Urgent!-example-1
User Tarulen
by
5.3k points
7 votes

=
log_( 3)({x}^(2) - 4) - log_(3)(x - 2) + log_(3)(x)

=
log_( 3)(\frac{{x}^(2) - 4}{x - 2}) + 2 × 1

=
log_( 3)(((x-2)(x+2))/(x - 2)) + 2 × 1

=
log_( 3)(x+2) + 2 × 1

User Emtrane
by
5.4k points